Building Serious Games to Exercise Computational Thinking: Initial Evaluation with Teachers of Children on the Autism Spectrum - Katherin Felipa Carhuaz Malpartida; Kamila Rios da Hora Rodrigues (Journal on Interactive Systems)
Computational Thinking (CT) is a reasoning process focusing on problem-solving and developing cognitive skills. Serious games are an effective tool for exercising these skills, as they offer a playful and versatile approach that can be adapted to different audiences. This work presents the design of a serious digital game designed to help enhance cognitive skills in children with Autism Spectrum Disorder (ASD), using the fundamental principles of CT. The first game design phase was completed and submitted for evaluation by professionals in the Education field from a collaborating institution. The observations made and the feedback obtained are being discussed with the development and research teams so that the game can be implemented.